Air Permeability and Moisture Management Properties of Electrospun Nanofiber Membranes (Journal of Fiber Bioengineering and Informatics, 2016)
Recently, electrospun nanofiber membranes (ENMs) have been received an increased attention in personalprotective clothing owing to their excellent filtration efficiency and low basis weight as filtering materials.However, high resistance to air flow is a major drawback of ENMs which in turn effect on comfort. Inaddition, comfort properties such as moisture management of ENMs need to be evaluated for practicalapplications. It is argued that air permeability and moisture management influenced by selection ofelectrospinning process parameters. This research studied the effect of collector speed and depositiontime on the air permeability of ENMs. Polyacrylonitrile nanofibers that had the diameter in the rangeof 291--877 nm were fabricated. The deposition time significantly influenced air permeability, unlikecollector speed. Hence a short deposition time is desirable. A good correlation was found between thetheoretical porosity and experimental air permeability of ENM. Furthermore, it was found that moisturemanagement properties of ENM require improvements for personal protective clothing.
Keywords: Electrospinning; Air Permeability; Moisture Management; Porosity; Nanofiber Membrane